A STUDY TO EVALUATE CHILD-FRIENDLY NEIGHBOURHOODS THROUGH A SET OF CHILDFRIENDLY INDICATORS - Abdullah, Alias; Nik Muhammad, Nik Munerahanim (PLANNING MALAYSIA, 2006)
Children' constitute the majority of the world's population (UNICEF 1998). They represent the survival of humankind to ensure the continuation of the next generation. Children were born into this world, by nature weak in body, senses and mind. Children are eager to accept education from day to day out of their inner curiosity. Hence, understanding children and creating a good and healthy environment must go hand in hand. In relations, providing a safe environment for children to live, play, run errands, and interacts with others are urban planning priority. However, most of the time, urban designs and housing setting are planned specifically for adults without taking into considerations the needs of the growing number of children. Children must be provided with the most supportive environment possible in order to enhance their capability in coping with their surroundings as well as to increase their capabilities to face challenges in future. For the purpose of these, this paper will have an in-depth study regarding the child-friendly environment, and how the neighbourhoods should be in order to create a safe environment for children. This study has selected three neighbourhoods to be evaluated in terms of the degree of their friendliness towards children. A set of Child-Friendly Indicators is applied as a tool for assessing and evaluating these three neighbourhoods. This paper focuses on diverse aspects pertaining to the child-friendly environment especially on the physical aspects. It will also share some of the recommendations to counter various issues in terms of planning for safe neighbourhoods in the future, as well as the recommendations to improve the developed Child-Friendly Indicators.